Hepatic mitochondrial signaling as a systemic hub: inter-organ communication networks in aging and aging-related diseases - Ji, Yishuo; Wang, Ying; Yu, Xiaowei; Jin, Yi; Zhao, Kai; Hu, Yue; He, Zhenglin (Frontiers in Cell and Developmental Biology, 2026)
Aging and aging-related diseases are increasingly viewed as systemic disorders arising from disrupted inter-organ communication, yet the mechanisms linking local metabolic stress to organism-wide dysfunction remain unclear. The liver occupies a central position in this network, but how hepatic mitochondrial stress is translated into circulating signals that remodel distant tissues is incompletely understood. Here, we synthesize evidence identifying hepatic mitochondria as a systemic signaling hub that integrates metabolic and inflammatory stress and disseminates blood-borne cues during aging. We focus on three major classes of mitochondrial outputs: UPRmt-driven mitokines, including fibroblast growth factor 21 (FGF21) and growth differentiation factor 15 (GDF15); metabolites generated through mitochondrial metabolic reprogramming; and mitochondrial danger signals such as mitochondrial reactive oxygen species (mtROS) and oxidized mitochondrial DNA (mtDNA). These signals act through endocrine, metabolic, and immune pathways to reshape mitochondrial function, inflammation, and energy homeostasis across multiple organs. We further discuss how aging shifts hepatic mitochondrial signaling from adaptive to maladaptive states and emphasize that liver-centered regulation operates within bidirectional networks involving the gut, skeletal muscle, and immune system. Finally, we outline translational challenges and potential strategies for modulating hepatic mitochondrial outputs to restore systemic homeostasis in aging and aging-related diseases.